Telessaúde no Brasil Durante a Pandemia do Novo Coronavírus - Lemos, Débora de Sousa; Medeiros, Adeli Regina Prizybicien de; Zanesco, Camila; Oliveira, Lucas Ferrari de; Gonçalves, Luciana Schleder (Computação Brasil, 2020)
O artigo discute a oferta de serviços de saúde a distância durante a pandemia da Covid-19.